The Role of Student Affairs Vice Principals in Enhancing the Effectiveness of Student Admission Processes - Riyan Adi Prayoga; Muh Jalaludin; Rezaabdul Wahab M; Muh Sabana Badar (Journal of Educational Management Research, 2026)
This study aims to examine the implementation of student affairs management in the student admission process and to evaluate its effectiveness in selecting students aligned with the school’s educational vision. A descriptive qualitative approach was employed, utilizing observations, in-depth interviews with the vice principal for student affairs, guidance and counseling teachers, duty teachers, and analysis of supporting documents. The findings reveal that the admission process is conducted through structured stages, including registration, academic assessment, Qur’an reading tests, interviews, and re-registration. The integration of disciplinary regulations, religious mentoring, counseling services, and extracurricular activities strengthens the effectiveness of student affairs management in the admission system. These mechanisms contribute to the selection of students who demonstrate discipline, strong character, and readiness to engage in vocational education within a boarding school context. The study implies that a well-managed and integrated student admission system plays a crucial role in enhancing student quality and supporting character education. Effective collaboration between school management and boarding-based educational programs is essential for ensuring sustainable student development and institutional effectiveness.